RANCANG BANGUN LOCAL CLOUD SERVER DENGAN NEXTCLOUD PADA CENTOS 7 DI SRH TRAINING CENTER - Ifvan Limalasa Mayendra; Herman Saputra; Uswatun Hasanah (JUTSI: Jurnal Teknologi dan Sistem Informasi, 2021)
Abstract: The file becomes an important thing in any case. Especially in the world of education which is something that can‟t be avoided that students must be able to create and save files correctly, both assignments and reports. Files stored on a computer do not guarantee that the data will be forever stored, because every month a computer maintenance must be held in a computer laboratory. Local cloud server technology with Nextcloud that uses the CentOs 7 operating system is very suitable to be applied in the SRH Training Center laboratory as a means of storing files and managing files in a Local Area Network. In this study the local cloud server was built with apache web server and mysql database and also with several packages supporting the Nextcloud application. With the construction of a local cloud server system with Nextcloud, students and teaching staff can easily manage the required learning files. Keywords: CentOs 7, Local Area Network, Local Cloud Server, Nextcloud, Web Server.  Abstrak: File menjadi suatu hal yang penting dalam hal apapun. Apalagi di dunia pendidikan yang menjadi suatu hal yang tidak bisa dihindari bahwa siswa harus mampu membuat dan menyimpan file dengan benar, baik itu tugas maupun laporan. File yang disimpan dalam komputer tidak menjamin data akan selamanya tersimpan, karena setiap bulan pasti diadakan maintenance komputer yang ada di laboratorium komputer. Teknologi local cloud server dengan Nextcloud yang menggunakan sistem operasi CentOs 7 sangat cocok diterapkan dalam laboratorium SRH Training Center sebagai sarana penyimpanan file dan memanajemen file dalam satu jaringan Local Area Network. Pada penelitian ini local cloud server dibangun dengan web server apache dan database mysql dan juga dengan beberapa paket pendukung aplikasi Nextcloud. Dengan dibangunnya sistem local cloud server dengan Nextcloud, maka siswa-siswi dan tenaga pengajar dapat mudah dalam memanejemen file pembelajaran yang dibutuhkan. Kata Kunci: CentOs 7, Local Area Network, Local Cloud Server, Nextcloud, Web Server.